Identification of functional divergence sites in dopamine receptors of vertebrates. (December 2019) - Xin, Juncai; Fan, Ting; Guo, Pan; Wang, Ju
Graphical abstract: Highlights: Dopamine receptors are evolved from a common ancestor after multiple gene duplication events and functional divergence. Sites specific on each receptor can be identified by comparing their protein sequences in the context of evolution. Altered functional constraints or different evolutionary rates may have taken place at some amino acids in the receptors. Most of the potential peptide sites related to functional divergence are included in ICL3, M6 and M7 domains. The functional divergence sites provide molecular basis for further dopamine receptor function exploration. Abstract: Dopamine is one of the major neurotransmitters in the brain and body, and regulates a wide variety of functions via its binding with dopamine receptors. Abnormalities in dopamine receptors have also been found to be related to various neurological disorders. For such reason, dopamine receptors are among the key components to understanding the molecular mechanisms of many diseases, they are also the potential drug targets for the treatment of many diseases. Till now, five different dopamine receptors (D1-D5) have been identified in mammals, which are assumed to be evolved from a common ancestor after multiple gene duplication events and functional divergence. Thus, identifying the specific features of each dopamine receptor, will not only provide clues for understanding the functional differences between the receptors, but also help us to design drugs specific for a certain subtype of receptor. In this study, we investigated the functional divergence in dopamine receptors in representative vertebrate species by analyzing their molecular evolution features. Our results showed that the coefficients for type I functional divergence (θI ) were significantly greater than 0 for all the pairwise comparisons between the five dopamine receptors, suggesting that type I functional divergence, i.e., altered functional constraints or different evolutionary rates, may have taken place at some amino acids in the receptors. We further identified 84 potential type I functional divergence peptide sites for the pairwise comparisons between the D1-like and D2-like are identified in total. When these sites were mapped to the 3D structure of dopamine receptors, most of them were included in ICL3, M6 and M7 domains. Especially, sixteen of these sites may be the major sites associated with the changes of properties between D1-like and D2-like receptors. These sites provide molecular basis for further studies such as dopamine receptor function exploration and subtype specific drug design and screening.